Wild boar in focus: initial model outputs of wild boar distribution based on occurrence data and identification of priority areas for data collection. Issue 1 (11th January 2019) - ,; Croft, Simon; Smith, Graham; Acevedo, Pelayo; Vicente, Joaquín
Abstract : By reviewing the different types of data targeted by the ENETWILD Wild Boar Data Collection Model (occurrence, hunting bag, abundance data) that have become available, an initial model could be built with occurrence data. A preliminary model analysis was performed to estimate the likely distribution of wild boar comparing the performance of a presence‐only model (bioclim) and presence‐background model (MaxEnt). Based on the results of this modelling, locations were identified, notably in Eastern Europe, where more data are required in order to produce more robust model projections of occurrence. This report also outlines the current state of available data collected by ENETWILD (occurrence, hunting bag and density) on wild boar and the development of a model framework that can be used to produce outputs on the yearly density distributions at high resolution of wild boar at a European scale.